2014
DOI: 10.1088/2041-8205/781/2/l33
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Weak Wind From the Young Sun

Abstract: The early history of the solar wind has remained largely a mystery due to the difficulty of detecting winds around young stars that can serve as analogs for the young Sun. Here we report on the detection of a wind from the 500 Myr old solar analog π 1 UMa (G1.5 V), using spectroscopic observations from the Hubble Space Telescope. We detect H i Lyα absorption from the interaction region between the stellar wind and interstellar medium, i.e., the stellar astrosphere. With the assistance of hydrodynamic models of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
191
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(213 citation statements)
references
References 41 publications
17
191
5
Order By: Relevance
“…From our models, we find power laws ofṀ ∝ F 0.30±0.02 X andṀ ∝ F 0.67±0.10 X for the Parker and CS models respectively when accounting for the low activity stars only (solid blue lines). If we include the whole sample in our fits, we obtainṀ ∝ F 0.38±0.01 Wood et al (2014) below their wind dividing line although the power law value they find is higher than ours. The main difference between our models and the results of Wood et al (2014) is the behaviour at high X-ray flux.…”
Section: Comparison With Other Workcontrasting
confidence: 67%
See 1 more Smart Citation
“…From our models, we find power laws ofṀ ∝ F 0.30±0.02 X andṀ ∝ F 0.67±0.10 X for the Parker and CS models respectively when accounting for the low activity stars only (solid blue lines). If we include the whole sample in our fits, we obtainṀ ∝ F 0.38±0.01 Wood et al (2014) below their wind dividing line although the power law value they find is higher than ours. The main difference between our models and the results of Wood et al (2014) is the behaviour at high X-ray flux.…”
Section: Comparison With Other Workcontrasting
confidence: 67%
“…Numerical values for the mass-loss rates can be found in Table A.1. Additionally, we have overplotted the data presented by Wood et al (2014) in red (see their Fig. 4).…”
Section: Comparison With Other Workmentioning
confidence: 99%
“…In the inner Solar System, stellar wind drag is roughly 30% as effective as Poynting-Robertson drag in removing small particles (Gustafson 1994). Observations of the youngest solar-type stars suggest mass loss rates 10 times the mass loss rateṀ of the current Sun (Wood et al 2014, and references therein). Theoretical studies predict mass loss rates up to 100Ṁ (e.g., Cohen & Drake 2014;Airapetian & Usmanov 2016).…”
Section: Neat Planet Formation In a Remnant Gas Diskmentioning
confidence: 99%
“…The solar wind speed and flux evolution with time are suggested by the observations of young solar analogs. Wood et al (2014) observed the Lyman alpha absorption from the interaction between the stellar wind and the interstellar medium and reconstructed the intensity of the solar wind at various ages of solar-type stars. They concluded that the solar wind flux might have initially increased by few orders of magnitude with respect to current solar wind conditions during the first 700 Myr of solar-type star and then decreased down to the current flux.…”
Section: A Mixed Particle/radiation Effect: Atmospheric Escape-the Camentioning
confidence: 99%